2013
DOI: 10.5430/jnep.v3n11p28
|View full text |Cite
|
Sign up to set email alerts
|

Pressure ulcers in the adult intensive care unit: a literature review of patient risk factors and risk assessment scales

Abstract: Background: Critically ill patients are at high risk for pressure ulcer (PrU) development due to their high acuity and the invasive nature of the multiple interventions and therapies they receive. With reported incidence rates of PrU development in the adult critical care population as high as 56%, the identification of patients at high risk of PrU development is essential. This paper will explore the association between PrU development and risk factors. It will also explore PrU development and the use of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 54 publications
6
34
0
1
Order By: Relevance
“…[25] Consequently, their physical activity is severely limited and their intake of nutrients is likely to be insufficient. [26] All of these factors could place ICU patients at greater risk of PU development.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Consequently, their physical activity is severely limited and their intake of nutrients is likely to be insufficient. [26] All of these factors could place ICU patients at greater risk of PU development.…”
Section: Discussionmentioning
confidence: 99%
“…With reported incidence rates of bedsore development in the adult critical care population as high as 56%; the identification of patients at high risk of bedsore development is essential. This paper will explore the association between bedsore development and risk factors 8 . Pressure ulcer risk assessment is a component of the assessment process used to identify individuals at risk of developing a pressure ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…Explanations for the varying rates are likely to be with the various methods used to calculate incidence, particularly with the varying categories of pressure ulcers included in the calculations, plus whether those pressure ulcers included were truly critical care acquired. Despite the varying incidence, pressure ulcers are often preventable (NICE, ) and pressure ulcer assessment is an important first step in the prevention of serious consequences such as pain, scaring and increased likelihood of survival (Alderden et al , ; Tayyib et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients have an increased incidence of pressure ulcers when compared to other acute care areas (Brindle, ; Alderden et al , ; Lahmann et al , ; Cox, ; Tayyib et al , ) and within critical care variation exists in the reported incidence. Recently, pressure ulcer incidence was calculated in an intensive and high dependency unit in Finland and was found to be 11.1% (Ahtiala et al , ).…”
mentioning
confidence: 99%